Engineering Materials and Process Technologies: 2nd Conference of Programme Groups of the Faculty of Mechanical Engineering University of Maribor, Book of Abstracts (University of Maribor Press, 2025)
The publication presents an overview of the research achievements of Programm Groups of the Faculty of Mechanical Engineering: P2-0424 Design of Novel Properties of (Nano)Materials & Applications, P2-0063 Design of Cellular Structures, P2-0120 Technologies of Metastable Materials, P2-0118 Textile Chemistry and Advanced Textile Materials, and P2-0196 Research in Power, Process, and Environmental Engineering from 2024 to 2025. Members of the program group present their research innovations and progress achieved within the framework of the program group’s activities.